TRACE ELEMENT FRACTIONATION DURING FLUID-INDUCED ECLOGITIZATION IN A SUBDUCTING SLAB: TRACE ELEMENT AND LU-HF-SM-ND ISOTOPE SYSTEMATICS - John T.; Haase K.; Schenk V.; Scherer E.E. (My University, 2004)
Spatially closely associated gabbros and eclogites of central Zambia represent relics of subducted oceanic crust in a suture zone. The eclogites, which formed at 630–690 °C and 2.6–2.8 GPa, yield Lu–Hf ages between 607±14 and 659±14 Ma, suggesting that subduction was active for at least 24 Myr. The trace element- and isotope compositions of the gabbros and eclogites range from those of incompatible-element depleted gabbros from the lower oceanic crust to those of enriched ocean–island basalts. Several eclogites display a large fractionation of the light rare earth elements from heavy rare earth- and high field strength elements, an effect that cannot be of magmatic origin but must have resulted from the passage of fluids through the rocks during metamorphism. In some samples, fluid pathways are marked by veins of eclogite facies minerals. Garnet-whole rock ages based on the Sm–Nd (relatively mobile) and Lu–Hf (relatively immobile) systems are identical, consistent with light rare earth elements being fractionated during eclogitization. Modeling using fluid–mineral partition coefficients suggests that the fractionated rocks have reacted with an amount of fluid equal up to 80% of their mass. The most likely source for such a large volume of fluid is the serpentinized lithospheric mantle of the subducting slab. The Zambian eclogites and their veins represent relict fluid pathways through subducted oceanic crust and provide direct evidence for channelized fluid flow and element transport within a slab. The transformation of dry, metastable slab gabbros to eclogites upon fluid-infiltration, accompanied by the transport of fluid-mobile elements, could be responsible for generating the slab component in arc magmas.